2021
DOI: 10.3390/molecules26154444
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Cucurbitane-Type Triterpenoids from Momordica charantia Fruit on Lipopolysaccharide-Stimulated Pro-Inflammatory Cytokine Production in Bone Marrow-Derived Dendritic Cells

Abstract: The bitter melon, Momordica charantia L., was once an important food and medicinal herb. Various studies have focused on the potential treatment of stomach disease with M. charantia and on its anti-diabetic properties. However, very little is known about the specific compounds responsible for its anti-inflammatory activities. In addition, the in vitro inhibitory effect of M. charantia on pro-inflammatory cytokine production by lipopolysaccharide (LPS)-stimulated bone marrow-derived dendritic cells (BMDCs) has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…These authors [ 43 ] also established that M. lucida extracts attenuated systemic inflammation (with fever) induced by LPS in rats and upregulated the anti-inflammatory cytokine, IL-10. Another study [ 44 , 45 ] demonstrated that cucurbitane-type triterpenoids compounds isolated from M. charantia could inhibit the production of IL-6 in LPS-stimulated bone marrow-derived dendritic cells, and the authors attributed these anti-inflammatory effects to interactions of hydrogen bonds between the protein residues and hydroxyl groups and sugar rings of triterpenoids compounds.…”
Section: Discussionmentioning
confidence: 99%
“…These authors [ 43 ] also established that M. lucida extracts attenuated systemic inflammation (with fever) induced by LPS in rats and upregulated the anti-inflammatory cytokine, IL-10. Another study [ 44 , 45 ] demonstrated that cucurbitane-type triterpenoids compounds isolated from M. charantia could inhibit the production of IL-6 in LPS-stimulated bone marrow-derived dendritic cells, and the authors attributed these anti-inflammatory effects to interactions of hydrogen bonds between the protein residues and hydroxyl groups and sugar rings of triterpenoids compounds.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a pro-inflammatory cytokine readily produced in cases of infections and tissue injuries (28) . Cao (29) demonstrated that cucurbitane-type triterpenoids compounds isolated from the fruit of M. charantia with IC 50 values of 0.028 to 1.962 µM could inhibit the production of IL-6 in LPS-stimulated bone marrow-derived dendritic cells, and the authors attributed these effects to interactions of hydrogen bonds between the protein residues and hydroxyl groups and sugar rings of triterpenoids compounds, which were visualized by molecular docking. Another study showed that the expression of IL-6 in adipose tissues and brown adipose tissues of diet-induced obese mice was lower in animals fed with the fruit of M. charantia in the concentrations of 2% and 5% (30) , the authors associated these results to the improvement of insulin resistance and fat deposition in the rodent model.…”
Section: Discussionmentioning
confidence: 99%
“…The general procedures were carried out similarly to those cited in previous papers with slight modi cations [42,23,27]. Biological and chemical reagents were obtained from Sigma (Missouri, USA).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%